2020
DOI: 10.1002/esp.5011
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring soil erosion on agricultural land: results and implications for the Rother valley, West Sussex, UK

Abstract: Monitoring has played a key role in understanding the rates, extent and frequency of erosion on agricultural land and this includes projects in Switzerland, Germany and the UK. In this case we focus on highly erodible soils in the Rother valley, West Sussex, southern England on which grow a range of arable crops throughout the year. Erosion rates and extent are high, particularly in response to exceptionally wet periods in the early winter. In the monitored period, rates on summer crops were relatively low due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
0
12
0
Order By: Relevance
“…Previous studies have shown similar patterns of lower microplastic concentrations, with losses of 30-45% from soils, following heavy rainfall events (8). In addition, the resulting erosion of agricultural land is seasonal, with increased erosion prevalent in winter months (54). This will depend on the soil type as more dense soils are more susceptible to runoff and will therefore likely retain less plastic (8).…”
Section: Discussionmentioning
confidence: 79%
“…Previous studies have shown similar patterns of lower microplastic concentrations, with losses of 30-45% from soils, following heavy rainfall events (8). In addition, the resulting erosion of agricultural land is seasonal, with increased erosion prevalent in winter months (54). This will depend on the soil type as more dense soils are more susceptible to runoff and will therefore likely retain less plastic (8).…”
Section: Discussionmentioning
confidence: 79%
“…An example of this is maps of around 200 fields in the Rother valley, West Sussex, UK (Figure 3), which have a history of erosion in the last 30 years. We can also identify which of these fields (66%) are potentially connected to the freshwater system and therefore potential pollution sources (Boardman et al, 2020; Favis‐Mortlock et al, 2022). This enables mitigation measures to be planned for vulnerable fields.…”
Section: Discussionmentioning
confidence: 99%
“…A basic mitigation measure is to interrupt water and/or sediment connectivity within agricultural catchments. Many major erosion events and much off‐site damage is the result of flow of runoff from one field to another (Biddulph et al, 2017; Boardman et al, 2020; Evans & Boardman, 2003; Wainwirght et al, 2011; Wilkinson et al, 2014). Large blocks of fields under the same land use are likely to be bare at the same time: the coincidence of lack of vegetation cover and rainfall may then lead to runoff and erosion.…”
Section: The Need For a Comprehensive Mitigation Strategymentioning
confidence: 99%
See 1 more Smart Citation
“…Occasionally, unexpected rainfall occurs following irrigation. On fields without a tile drainage system, this can make the soil too wet, turning a water deficit problem into a water excess problem, which may result in crop yield and quality losses as well as soil erosion and nutrient leaching [64]. Determining the timing and amount of water for irrigation remains one of the biggest knowledge gaps for supplemental irrigation in AC [18,23].…”
Section: Supplemental Irrigationmentioning
confidence: 99%